1993
DOI: 10.1159/000175868
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Baseline Major Risk Factors to Coronary and All-Cause Mortality, and to Longevity: Findings from Long-Term Follow-Up of Chicago Cohorts

Abstract: The focus here is on relationships between major risk factors and long-term mortality from coronary heart disease (CHD) and all causes, and on longevity, in Chicago cohorts: 25-year follow-up for Peoples Gas (PG) men aged 25-39 (n = 1,119), 30-year follow-up for PG men aged 40-59 (n = 1,235), 24-year follow-up for Western Electric (WE) men aged 40-55 (n = 1,882); also 15-year follow-up for five cohorts of the Chicago Heart Association (CHA) Study: men aged 25-39 (n = 7,873), 40-59 (n = 8,515), 60-74 (n = 1,490… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
0
4

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(156 citation statements)
references
References 33 publications
7
145
0
4
Order By: Relevance
“…Authors of numerous epidemiological studies conclude that tobacco smoking is associated with ca. 1.5 to 2.5 increase in the risk of developing CVD [16][17][18][19]. In Europe, 18% of deaths from CVD are attributable to tobacco smoking.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Authors of numerous epidemiological studies conclude that tobacco smoking is associated with ca. 1.5 to 2.5 increase in the risk of developing CVD [16][17][18][19]. In Europe, 18% of deaths from CVD are attributable to tobacco smoking.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…4 It is well known that the accumulation of risk factors for cardiovascular events increases the incidence of such events. In previously reported subanalyses of the MEGA Study involving patients with hypertension and diabetes, the incidence of cardiovascular events was higher than in patients without hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In addition, dyslipidaemia is a conventional risk factor for cardiovascular disease (CVD), and the presence of hypertension increases the incidence of CVD. [7][8][9] We previously reported that hypertension is a strong risk factor for coronary heart disease (CHD) 10 and stroke, 11 and that pravastatin is effective to prevent cardiovascular events in patients with hypertension in the MEGA Study.…”
Section: Introductionmentioning
confidence: 99%
“…42 It was pointed out that a cut in sodium consumption by both manufacturers and individuals of 100 mmol/24h could reduce the incidence of stroke by 39% and that of ischaemic heart disease by 30%, 43 and effect a marked reduction in mortality 44 and/or morbidity. 45 Such figures put the onus on the food industry to reduce the amount of salt added in food processing and help implement the recommendations made to the public for salt reduction. [46][47][48][49] It should be noted that the standard diet in the residents of our old peoples home did not include processed food in the first place; thus, lowered BP was achieved in them only by removing ordinary salt from the kitchen and the table and substituting it with Pansalt ® .…”
Section: Discussionmentioning
confidence: 99%